2003
DOI: 10.1016/s0002-9440(10)64332-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Diabetes Causes Breakdown of the Blood-Retina Barrier by a Mechanism Involving Tyrosine Nitration and Increases in Expression of Vascular Endothelial Growth Factor and Urokinase Plasminogen Activator Receptor

Abstract: The purpose of these experiments was to determine the specific role of reactive oxygen species (ROS) in the blood-retinal barrier (BRB) breakdown that characterizes the early stages of vascular dysfunction in diabetes. Based on our data showing that high glucose increases nitric oxide, superoxide, and nitrotyrosine formation in retinal endothelial cells, we hypothesized that excess formation of ROS causes BRB breakdown in diabetes. Because ROS are known to induce increases in expression of the well-known endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 55 publications
(58 reference statements)
8
177
0
2
Order By: Relevance
“…In parallel, analysis of oxidative stress and peroxynitrite markers showed significant increases in 4-HNE adducts and nitrotyrosine formation in aqueous humour samples from diabetic patients and diabetic rat retinas compared with non-diabetic controls. These results lend further support to previous studies showing enhanced peroxynitrite formation in clinical and experimental diabetes [1,3,12,22]. Treatment of our diabetic animals with atorvastatin exerted similar protective effects to FeTPPs in reducing peroxynitrite and 4-HNE adducts, as well restoring the balance between NGF and proNGF to normal levels.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In parallel, analysis of oxidative stress and peroxynitrite markers showed significant increases in 4-HNE adducts and nitrotyrosine formation in aqueous humour samples from diabetic patients and diabetic rat retinas compared with non-diabetic controls. These results lend further support to previous studies showing enhanced peroxynitrite formation in clinical and experimental diabetes [1,3,12,22]. Treatment of our diabetic animals with atorvastatin exerted similar protective effects to FeTPPs in reducing peroxynitrite and 4-HNE adducts, as well restoring the balance between NGF and proNGF to normal levels.…”
Section: Discussionsupporting
confidence: 91%
“…A growing body of evidence supports the concept that diabetes disturbs homeostasis in the retina by activating glial cells, reducing neurotrophic and prosurvival inputs, and increasing proinflammatory cytokines, leading to accelerated cell death and vascular permeability, thus impairing vision, notions which have been reviewed previously [18][19][20]. In agreement, we and others have reported that increases in proinflammatory cytokines, including vascular endothelial growth factor (VEGF), NGF, TNF-α, intercellular adhesion molecule-1 and inducible nitric oxide synthase, in diabetic retinas were correlated with neuronal cell death and vascular permeability [1,3,12,13,[21][22][23]. However, the role of neurotrophins in the diabetic eye remains unknown.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations